2018
DOI: 10.1017/age.2018.17
|View full text |Cite
|
Sign up to set email alerts
|

Economic Implication of Grazing and Water Resource Scarcity on Households’ Welfare and Food Security in Tigrai, Ethiopia

Abstract: In this paper, I have explored the link between grazing and water resource scarcity and per capita food consumption expenditure as a proxy for welfare and food security using distance and shadow price as a resource scarcity indicator in Northern Ethiopia based on a unique data set for 518 sample farmers. To address my objectives, I employed an IV 2SLS model for estimating welfare and probit for analyzing food security, drawing on a separable farm household model. My results confirmed the theoretical prediction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
0
3
0
1
Order By: Relevance
“…In the assessment of the effect of IFNFAs on household consumption, we opt for an instrumental variable approach to deal with the potential endogeneity between IFNFAs and consumption used as a proxy of household welfare (see Hadush, 2019). This is initially formulated in the following model:where i,j are respectively households and consumption indicators.…”
Section: Empirical Strategymentioning
confidence: 99%
“…In the assessment of the effect of IFNFAs on household consumption, we opt for an instrumental variable approach to deal with the potential endogeneity between IFNFAs and consumption used as a proxy of household welfare (see Hadush, 2019). This is initially formulated in the following model:where i,j are respectively households and consumption indicators.…”
Section: Empirical Strategymentioning
confidence: 99%
“…Todavia, requer proximidade geográfica, maior protagonismo dos consumidores na relação com produtores e políticas públicas adaptadas ao contexto local. No outro ponto, Hadush (2018), em estudo na Etiópia, verificou relação direta entre escassez de recursos hídricos e elevação no custo per capita dos alimentos consumidos, afetando negativamente o bem-estar e a segurança alimentar das famílias.…”
Section: O Acesso a Comunidades Indígenasunclassified
“…Several studies conducted in the country indicated that conflict and drought factors, such as land size, dependency ratio, credit services, family size, household assets, number of livestock, fertilizer usage, employment, household head age, sex, education, and social protection program (26, 27), can affect the household's food security (28)(29)(30)(31)(32)(33)(34). For food insecure countries, including Ethiopia, with the advantage of the two greatest potential resources, i.e., "the people and the productive land and water, " efficient usage of these resources by investing both people and productivity can mitigate the food security problem (1,35,36).…”
Section: Introductionmentioning
confidence: 99%